Human decimation caused bottleneck effect, genetic drift, and inbreeding in the Canarian houbara bustard. Issue 2 (13th December 2022) - Horreo, Jose L.; Ucero, Alberto; Palacín, Carlos; López‐Solano, Alfonso; Abril‐Colón, Inmaculada; Alonso, Juan C.
Abstract: An endangered subspecies of the African houbara bustard, the Canarian houbara ( Chlamydotis undulata fuertaventurae ), is endemic to the Canary Islands off southern Morocco (Lanzarote, Fuerteventura, and La Graciosa islands). This population decreased over the last centuries because of hunting and egg collection, and was close to extinction in Lanzarote around the middle of last century. Later, the species recovered because of hunting bans, but in Fuerteventura a significant decline has again occurred in the last decades and houbaras are on the brink of extirpation on that island. We describe the genetic characteristics and recent evolutionary history of this subspecies to provide essential information for the evaluation of the conservation actions implemented and for the development of new measures to prevent further declines and local extirpations. We amplified microsatellite loci to infer genetic variability, population structure, and gene flow. The subspecies exhibited relatively high genetic variability but reduced heterozygosity. In spite of high gene flow among locations and islands, we identified 2 genetic units: 1 comprising La Graciosa and Fuerteventura islands, and the other restricted to Lanzarote. We detected genetic bottlenecks and subsequent inbreeding in both units, with a reduced effective number of alleles in Lanzarote compared to Fuerteventura‐La Graciosa. This genetic structure may be explained by human‐induced historical population declines and an associated bottleneck effect, particularly in Lanzarote. Conservation measures should aim to recover the houbara population of Fuerteventura, improving survival of adults and juvenile productivity, and to ensure that genetic flow continues among breeding locations and islands to recover the original population structure (an unique genetic unit over the range of the species) and prevent further genetic deterioration, which could lead to extirpation of this endemic subspecies. Abstract : We describe the genetic characteristics and dynamics, and the recent evolutionary history of the Canarian houbara bustard, an endemic to the Canary Islands. We identified high gene flow and two genetic units, with genetic bottlenecks and subsequent inbreeding in both of them, and propose potential management actions to avoid its extinction.